National Survey on bladder and bowel dysfunctions in Autism Spectrum Disorder population - Gubbiotti, Marilena; Balzarro, Matteo; Zoccante, Leonardo; Di Gennaro, Gianfranco; Marchiafava, Moreno; Bedetti, Chiara; Rubilotta, Emanuele (Frontiers in Psychiatry, 2024)
INTRODUCTION To evaluate lower urinary tract symptoms (LUTS) and bowel disorders in a population of young subjects with autism spectrum disorder (ADS) by a national survey and to assess the relationship between the occurrence, frequency and type of LUTS and the severity of behavioral and neuropsychiatric characteristics. MATERIALS AND METHODS A survey on LUTS and bowel disorders in ASD population was send by mail and social media through the main Italian Associations of ASD between February and September 2022. Correlation between LUTS and ASD severity was also assessed. RESULTS The survey was completed by 502 subjects with a mean age of 16.6  10 years: males were 413 (mean age: 16.5  9.8 yrs), while females 89 (mean age: 17.2  10.9 yrs). ADS severity was found low in 29.9%, moderate in 27.1%, and severe in 43%. LUTS were reported by 77.1%, storage symptoms in 51.4%, and voiding symptoms in 60.6%. Urinary incontinence was reported by 12.5%. Enuresis was reported by 14.3% (72/502) of the respondents: primary enuresis in 70.8% (51/72), secondary in the remaining. Pads were used by 40 subjects with a median of 2.9 pads/day (range 0-8). A toilet training program was performed by 61 of the respondents, with satisfactory results in 40/61 (65.6%). A significant correlation was found between greater ASD severity and higher LUTS rates. Mean VAS score on the impact of LUTS on family relationship was: 2  2.9. Regular bowel function was reported by 57.4% (288/502) of the respondents, while increased daily defecations was present in 11.2% (56/502), constipation in 31.5% (158/502), and fecal incontinence in 7.9% (40/502). CONCLUSIONS This survey demonstrated that LUTS are very common in young ASD population and that urinary symptoms prevalence is related to a higher severity of ASD condition. Bowel disorders are often associated to urinary symptoms and dysfunctions. Urologists should be aware of the frequent occurrence of urological disorders and symptoms in individuals with ASD and should be involved in their clinical management in a multidisciplinary team that cares for these people.